Celebrations amongst challenges: Considering the past, present and future of the qualitative methods in psychology section of the British Psychology Society. Issue 3 (3rd July 2019) - Riley, Sarah; Brooks, Joanna; Goodman, Simon; Cahill, Sharon; Branney, Peter; Treharne, Gareth J.; Sullivan, Cath
ABSTRACT: This article summarises the standpoint of the Qualitative Methods in Psychology Section of the British Psychological Society regarding the current position of qualitative research in psychology in the United Kingdom. The article is in three parts. Part one documents the historical development of the section, outlining its rationale, remit, and current activities. These activities aim to champion and develop qualitative methods in psychology, supporting high quality work regardless of epistemological or ontological position. Part two considers the current context of our work, describing not only how qualitative methods are valued in the United Kingdom but also how this recognition is undermined, particularly through the operationalisation of our national research assessment (the Research Excellence Framework). We also consider the challenges that Open Science poses for qualitive researchers. Part three highlights some of the significant contributions of UK-based qualitative researchers to psychology, with a particular focus on feminist-informed research, discourse analysis, and interpretative phenomenological analysis, before pointing to future exciting possibilities based on research exploring the affordances of digital technologies and innovative synthesising across epistemologies and disciplinary boundaries.